Plan de marketing para la pañalera pototin franquicia Vinces, año 2012 - Mendoza Bran, Diana Magdalena (2013)
Developing Marketing Plan for the Pañalera Pototin the Keg is to increase by 20% in 2013 to improve its position in the market for the collection of information was. Elaborated wan questionnaires, one of ten questions 242 people, also obtained the primary and secondary information of the company. As a result we obtained that keep the Pañalera Pototin at the time any advertising or promotion in any media of the town, and its corporate image is not yet defined in the market for Vinces. To improve its market position in the development of a Marketing Plan for the Pañalera Pototin the Keg, in order to inform the population of Vinces and its surroundings, the portfolio of products offered. The Plan was developed Marketing Plan, promotion and publicity which produced a radio spot, a video for television, design for print, billboard, flyer. Was supplemented with the redesign of the corporate image, logo, slogan, business cards, leaflets, billboards, covers letterhead, envelopes and manila white, stickers, neon signs, uniform. We also created two promotions to customers and potential customers; it was a recommended to work in the home delivery because it is one of the services in greatest demand was surveyed Vinces market. It was recommended to the Pañalera Pototin the keg, advertising design strategies to achieve greater opportunities for business growth in the consumer market in the city of Vinces.